The Dynamics Existence of Renege Group Ahad Sunnah in Indonesia - Mufasiroh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The validity of mutawatir and ahad Sunnah has been a subject of debate since the post-sahabah era and subsequent generations. Some groups reject the existence of Sunnah altogether, while others do not accept ahad Sunnah as a source of law. These groups are known as inkar al-sunnah. This phenomenon is also found in Indonesia. This study aims to analyze the principles of groups that reject ahad Sunnah in determining sources of law, using qualitative methods with a content analysis approach to this concept. The findings reveal that inkar al-sunnah groups consider the Qur'an as a complete and definitive (qath’i) source, rendering the ahad Sunnah, which is considered speculative (dzann), unnecessary. Three categories of groups were identified: (1) groups rejecting Sunnah entirely; (2) groups rejecting Sunnah unless it has an empirical correlation with the Qur'an; and (3) groups not accepting ahad Sunnah, including Mu’tazilah and Orientalists. The study also identifies several doctrines of inkar al-sunnah in Indonesia: rejecting the obligation of prayer, zakat, fasting during Ramadan, and other religious practices. This research contributes to academic discourse by providing new insights into the inkar al-sunnah phenomenon in Indonesia and its impact on religious understanding and practices. However, this study has limitations, as it does not include an in-depth empirical exploration of the dynamics of these groups within society. Further research is recommended to explore the social and theological impacts of the inkar al-sunnah phenomenon in various regions and to analyze effective ways to address these theological challenges within Muslim communities.